Investigating the difference of face distinction between adult and infant for the design of service robots. (4th July 2022) - Yao, Lichang; Dai, Qi; Yu, Yiyang; Nishioka, Yuki; Wu, Qiong; Yang, Jiajia; Takahashi, Satoshi; Ejima, Yoshimichi; Wu, Jinglong
People's requirements for service robots are gradually increasing as their application scope expands and science and technology advance. When facing multiple objects, orderly service can no longer meet the needs of customers. Searching for clients in greater need and providing humanised services in a timely manner is a new task. This study uses human behaviour as a learning blueprint to investigate whether adults can respond quickly to infants. The results show that humans can respond quickly to infants. This could lead to the development of humanised service robots that prioritise infants as service objects and provide gentle service by recognising infant facial features.